A Tunable Microfluidic Device Enables Cargo Encapsulation by Cell‐ or Organelle‐Sized Lipid Vesicles Comprising Asymmetric Lipid Bilayers. Issue 7 (27th May 2019) - Romanov, Valentin; McCullough, John; Gale, Bruce K.; Frost, Adam
Abstract: Cellular membranes play host to a wide variety of morphologically and chemically complex processes. Although model membranes, like liposomes, are already widely used to reconstitute and study these processes, better tools are needed for making model bilayers that faithfully mimic cellular membranes. Existing methods for fabricating cell‐sized (µm) or organelle‐sized (tens to hundreds of nanometers) lipid vesicles have distinctly different requirements. Of particular note for biology, it remains challenging for any technique to efficiently encapsulate fragile cargo molecules or to generate liposomes with stable, asymmetric lipid leaflets within the bilayer. Here a tunable microfluidic device and protocol for fabricating liposomes with desired diameters ranging from ≈10 µm to ≈100 nm are described. Lipid vesicle size is templated by the simple inclusion of a polycarbonate filter within the microfluidic system and tuned with flow rate. It is shown that the vesicles made with this device are stable, unilamellar, lipid asymmetric, and capable of supporting transmembrane protein assembly, peripheral membrane protein binding, as well as soluble cargo encapsulation (including designer nanocages for biotechnology applications). These fabricated vesicles provide a new platform for studying the biophysically rich processes found within lipid–lipid and lipid–protein systems typically associated with cellular membranes. Abstract : Cellular membranes play host to a wide variety of morphologically and chemically complex processes. Liposomes are cellular mimics, capturing the complexity of the lipid bilayer. This work describes a microfluidic platform as a powerful tool for creating size (from ≈10 µm to ≈100 nm) and lipid distribution‐controlled liposomes capable of supporting transmembrane–protein assembly, peripheral‐membrane protein binding, as well as soluble cargo encapsulation.